2014
DOI: 10.1002/ppul.23058
|View full text |Cite
|
Sign up to set email alerts
|

Small airways dysfunction in long‐term survivors of pediatric stem cell transplantation

Abstract: Small airways dysfunction as measured by MBWN2 was a common finding at long term follow-up of children after allogeneic HSCT and was associated with cGvHD. The majority of these subjects had normal spirometric values and did not report any respiratory symptoms. Prospective studies are required to evaluate the long term clinical consequences of these signs of small airway disease and the value of MBWN2 as an early marker of pulmonary cGvHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…In cystic fibrosis, Gustafsson et al [32] have shown that peripheral airways are indeed involved. Similarly, in stem cell transplanted children [33] and in obliterating bronchiolitis after lung transplantation [34], peripheral lung function is affected. Thus, peripheral lung units are involved in fundamentally different lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In cystic fibrosis, Gustafsson et al [32] have shown that peripheral airways are indeed involved. Similarly, in stem cell transplanted children [33] and in obliterating bronchiolitis after lung transplantation [34], peripheral lung function is affected. Thus, peripheral lung units are involved in fundamentally different lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Green et al examined a group of primary ciliary dyskinesia patients of whom nearly all, including those with normal FEV 1 , had abnormal LCI 2.5 . Similar observations were also found in long‐term survivors of pediatric stem cell transplantation …”
Section: Discussionmentioning
confidence: 69%
“…However, PCD and CF differ considerably from HP according to basic pathology, infectious mucus retention/clearance and life‐long chronicity. Uhlving et al studied MBW N2 in pediatric stem cell recipients and found that one‐third of the patients had abnormal LCI 2.5 , despite normal spirometry in 90%. These findings are consistent with ours and in contrast to studies in asthmatic children and adolescents, where LCI 2.5 seems to be within or close to the normal range …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross‐sectional study of pediatric HSCT‐recipients, we have previously demonstrated abnormal LCI in 34% of patients at 3 to 10 years follow‐up, despite normal spirometry in a majority of patients . Nyilas et al found cGvHD score to be closely correlated to LCI value.…”
Section: Introductionmentioning
confidence: 83%